Anterior Spinal Overgrowth Is the Result of the Scoliotic Mechanism and Is Located in the Disc. Issue 11 (1st June 2017) - Brink, Rob C.; Schlösser, Tom P.C.; Colo, Dino; Vavruch, Ludvig; van Stralen, Marijn; Vincken, Koen L.; Malmqvist, Marcus; Kruyt, Moyo C.; Tropp, Hans; Castelein, René M.
Abstract : Study Design: Cross-sectional study. Objective: To investigate the presence and magnitude of anterior spinal overgrowth in neuromuscular scoliosis and compare this with the same measurements in idiopathic scoliosis and healthy spines. Summary of Background Data: Anterior spinal overgrowth has been described as a potential driver for the onset and progression of adolescent idiopathic scoliosis (AIS). Whether this anterior overgrowth is specific for AIS or also present in nonidiopathic scoliosis has not been reported. Methods: Supine computed tomography (CT) scans of thirty AIS patients (thoracic Cobb 21–81°), thirty neuromuscular (NM) scoliotic patients (thoracic Cobb 19–101°) and 30 nonscoliotic controls were used. The difference in length in per cents between the anterior and posterior side {[(ΔA-P)/P]*100%, abbreviated to A-P%} of each vertebral body and intervertebral disc, and between the anterior side of the spine and the spinal canal (A-C%) were determined. Results: The A-P% of the thoracic curves did not differ between the AIS (+1.2 ± 2.2%) and NM patients (+0.9 ± 4.1%, P  = 0.663), both did differ, however, from the same measurements in controls (–3.0 ± 1.6%; P  < 0.001) and correlated linearly with the Cobb angle (AIS r = 0.678, NM r = 0.687). Additional anterior length was caused by anterior elongation of the discs (AIS: A-P% disc +17.5 ± 12.7% vs. A-P% body –2.5 ± 2.6%; P  < 0.001, NM: A-P% disc +19.1 ± 18.0% vs. A-P% body –3.5 ± 5.1%; P  < 0.001). The A-C% T1-S1 in AIS and NM patients were similar (+7.9 ± 1.8% and +8.7 ± 4.0%, P  = 0.273), but differed from the controls (+4.2 ± 3.3%; P  < 0.001). Conclusion: So called anterior overgrowth has been postulated as a possible cause for idiopathic scoliosis, but apparently it occurs in scoliosis with a known origin as well. This suggests that it is part of a more generalized scoliotic mechanism, rather than its cause. The fact that the intervertebral discs contribute more to this increased anterior length than the vertebral bodies suggests an adaptation to altered loading, rather than a primary growth disturbance. Level of Evidence: 4